Effects of very high stimulation frequency and wide-pulse duration on stimulated force and fatigue of quadriceps in healthy participants - Kitima Rongsawad (2018)
© 2018 by Korean Academy of Rehabilitation Medicine. Objective To determine the effect of very high stimulation frequency (150 and 200 Hz) with wide pulse duration versus 50 Hz with wide pulse duration on stimulated force and fatigue of quadriceps femoris in healthy participants. Methods Thirty-four healthy participants underwent fatigue test using three stimulation frequency conditions (50, 150, and 200 Hz) with pulse duration of 0.9 ms. Normalized force values at the end of each fatigue protocol and curve fitting patterns were compared among stimulated frequencies. Results Very high stimulation frequency (150 and 200 Hz) conditions showed a trend of having more decline in normalized stimulated force during fatigue test compared to a low stimulation frequency at 50 Hz. However, the difference was not statistically significant. Responder group showed the same slope of a linear fitting pattern, implying the same pattern of muscle fatigue among three stimulation frequency conditions (-3.32 in 50 Hz, -2.88 in 150 Hz, and -3.14 in 200 Hz, respectively). Conclusion There were high inter-subject variations in the response to different frequency stimulation conditions. However, very high stimulation frequency generated the same fatigue pattern as the low stimulation frequency in the responder group. Further research is needed to explore the mechanism involved.